Thiamine for prevention of postoperative delirium in patients undergoing gastrointestinal surgery: A randomized clinical trial - Rohollah Moslemi; Hossein Khalili; Mostafa Mohammadi; Zeinab Mehrabi; Niayesh Mohebbi (Wolters Kluwer Medknow Publications, 2020)
Objective: Postoperative delirium is a common complication after gastrointestinal surgery that is associated with adverse outcomes. Thiamine is an essential cofactor for the glycolysis, oxidative metabolism, production of neurotransmitters in the crebs cycle. In this study, efficacy of thiamine was assessed as a preventive strategy of delirium in patients undergoing gastrointestinal surgery. Methods: In this randomized clinical trial, 96 adult patients admitted to the intensive care unit (ICU) following gastrointestinal surgery were included. Patients were allocated to receive either 200 mg intravenous thiamine daily or an equal volume of 0.9% saline for 3 days. Delirium was evaluated twice daily based on the confusion assessment method-ICU. The incidence of postoperative delirium was considered as the primary outcome, and total analgesic use and ventilation days has been defined as secondary outcomes of the study. Findings: The incidence rate of delirium was significantly lower in the thiamine group than the placebo group on the first day (8.3% vs. 25%; Odds ratio: 0.27 [95% confidence interval (CI): 0.08-0.92]; P= 0.026) and on the second day (4.2% vs. 20.8%; or: 0.16 [95% CI: 0.03-0.81]; P= 0.014). No adverse effect related to thiamine was detected during the study course. Conclusion: Study results suggest that thiamine is a safe option for the prevention of postoperative delirium in patients after gastrointestinal surgery.